2004
DOI: 10.1002/jnr.20240
|View full text |Cite
|
Sign up to set email alerts
|

Role for calcium‐activated potassium channels (BK) in growth control of human malignant glioma cells

Abstract: Voltage-dependent large-conductance Ca 2+ -activated K + channels, often referred to as BK channels, are a unique class of ion channels coupling intracellular chemical signaling to electrical signaling. BK channel expression has been shown to be up-regulated in human glioma biopsies, and expression levels correlate positively with the malignancy grade of the tumor. Glioma BK channels (gBK) are a splice variant of the hslo gene, are characterized by enhanced sensitivity to [Ca 2+ ] i , and are the target of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
99
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 53 publications
6
99
0
Order By: Relevance
“…The oncogenic role of KCNMA1 found in this study is in line with the previously reported growth inhibition of human astrocytoma by IBTX (Basrai et al, 2002;Weaver et al, 2004). Interestingly, the intermediate conductance K þ channel (IK) rather than KCNMA1 has been proposed to be important for PC-3 and LNCaP cells by Parihar et al (2003).…”
Section: Discussionsupporting
confidence: 90%
“…The oncogenic role of KCNMA1 found in this study is in line with the previously reported growth inhibition of human astrocytoma by IBTX (Basrai et al, 2002;Weaver et al, 2004). Interestingly, the intermediate conductance K þ channel (IK) rather than KCNMA1 has been proposed to be important for PC-3 and LNCaP cells by Parihar et al (2003).…”
Section: Discussionsupporting
confidence: 90%
“…Our data indicate that Ca 2+ -activated K + channels might participate in this process (Weaver et al, 2004) and we have recently identified two water channels (AQP 1 and 4) in glioma cells (McCoy and Sontheimer, 2005). In most cells, water permeability does not limit the regulation of cell size and cell volume (King et al, 2000) and we assume that this is also the case here.…”
Section: Discussionsupporting
confidence: 57%
“…4,32,33 Our in vitro experiments using either paxilline or hSlo knockdown indicate that BK channels do not play an essential role in Cal72 cell proliferation.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, we and others have shown that BK channels are a unique class of ion channels that are activated by a change in intracellular calcium, in voltage 2 and by a wide variety of molecules and molecular mechanisms including growth factors and hypoxia that, interestingly, are involved in carcinogenesis. [3][4][5][6] BK channels are expressed in a broad spectrum of cells in which they play a crucial role in neurotransmitter release, muscle relaxation 7,8 and diverse activities involved in tumor-associated processes such as cell proliferation, survival, secretion and migration. [9][10][11] Importantly, in human glioma, BK channels are significantly up-regulated, and their expression levels seem to correlate positively with tumor grade and poor patient prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation